Representaciones éticas de masculinidades hegemónicas - Zaida Godoy Navarro (Recherches, 2023)
This work explores the role of the North Border theater in the mythology of the drug trafficker; that is to say, it analyzes through which traits the drug traffickers in the studied works intend to build their masculinities and if these coincide with the portrait that the authorities are interested in disseminating. Specifically, she analyze Guerrero Negro (1988) and Fugitivos (1992) by Víctor Hugo Rascón Banda, La zona del silencio (2002) by Antonio Zúñiga, and Yamaha 300 (2004) by Cutberto López. It will point to how, the deeper we go into the 21st century, the greater the empathic distance towards drug traffickers, since the hedonism and ultraviolence of the most contemporary characters depoliticize the works.